Genomics of the Genus Bifidobacterium Reveals Species-Specific Adaptation to the Glycan-Rich Gut Environment - Milani, Christian (Appl Environ Microbiol, 2016)
Bifidobacteria represent one of the dominant microbial groups that occur in the gut of various animals, being particularly prevalent during the suckling period of humans and other mammals. Their ability to compete with other gut bacteria is largely attributed to their saccharolytic features. Comparative and functional genomic as well as transcriptomic analyses have revealed the genetic background that underpins the overall saccharolytic phenotype for each of the 47 bifidobacterial (sub)species representing the genus Bifidobacterium, while also generating insightful information regarding carbohydrate resource sharing and cross-feeding among bifidobacteria. The abundance of bifidobacterial saccharolytic features in human microbiomes supports the notion that metabolic accessibility to dietary and/or host-derived glycans is a potent evolutionary force that has shaped the bifidobacterial genome.